Genomic Analysis Revealed New Oncogenic Signatures in TP53-Mutant Hepatocellular Carcinoma - Kancherla, Venkatesh; Abdullazade, Samir; Matter, Matthias S.; Lanzafame, Manuela; Quagliata, Luca; Roma, Guglielmo; Hoshida, Yujin; Terracciano, Luigi M.; Ng, Charlotte K. Y.; Piscuoglio, Salvatore (Frontiers in Genetics, 2018)
The TP53 gene is the most commonly mutated gene in human cancers and mutations in TP53 have been shown to have either gain-of-function or loss-of-function effects. Using the data generated by The Cancer Genome Atlas, we sought to define the spectrum of TP53 mutations in hepatocellular carcinomas (HCCs) and their association with clinicopathologic features, and to determine the oncogenic and mutational signatures in TP53-mutant HCCs. Compared to other cancer types, HCCs harbored distinctive mutation hotspots at V157 and R249, whereas common mutation hotspots in other cancer types, R175 and R273, were extremely rare in HCCs. In terms of clinicopathologic features, in addition to the associations with chronic viral infection and high Edmondson grade, we found that TP53 somatic mutations were less frequent in HCCs with cholestasis or tumor infiltrating lymphocytes, but were more frequent in HCCs displaying necrotic areas. An analysis of the oncogenic signatures based on the genetic alterations found in genes recurrently altered in HCCs identified four distinct TP53-mutant subsets, three of which were defined by CTNNB1 mutations, 1q amplifications or 8q24 amplifications, respectively, that co-occurred with TP53 mutations. We also found that mutational signature 12, a liver cancer-specific signature characterized by T>C substitutions, was prevalent in HCCs with wild-type TP53 or with missense TP53 mutations, but not in HCCs with deleterious TP53 mutations. Finally, whereas patients with HCCs harboring deleterious TP53 mutations had worse overall and disease-free survival than patients with TP53-wild-type HCCs, patients with HCCs harboring missense TP53 mutations did not have worse prognosis. In conclusion, our results highlight the importance to consider the genetic heterogeneity among TP53-mutant HCCs in studies of biomarkers and molecular characterization of HCCs.